2013
DOI: 10.1227/neu.0b013e3182804662
|View full text |Cite
|
Sign up to set email alerts
|

Central Neurocytoma

Abstract: The long-term clinical outcomes of CN after multimodal treatment seem to be excellent. Our study suggests that treatment strategies for CN should focus on the patient's quality of life, as well as on tumor control, because of the benign nature of CN.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
25
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 49 publications
(25 citation statements)
references
References 23 publications
0
25
0
Order By: Relevance
“…Although with a low mobility, CN mainly occures in young adults [46], performs as a nonmalignant tumor, and may carry favorable prognoses with opportune treatment [7, 8]. All of these make it an important brain tumor worthy of attention.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Although with a low mobility, CN mainly occures in young adults [46], performs as a nonmalignant tumor, and may carry favorable prognoses with opportune treatment [7, 8]. All of these make it an important brain tumor worthy of attention.…”
Section: Discussionmentioning
confidence: 99%
“…CN often occurred in young adults [46]. Most CN were benign or borderline tumor, and of long-time survival with a gross total removal [7, 8]. However, for the low morbidity, only less than one thousand cases of CN have been reported in the world till today [9].…”
Section: Introductionmentioning
confidence: 99%
“…It has been 317 also shown that CUR decreased the levels of renal lipoperoxide 318 formation in both acute and chronic CCl 4 injuries [40,41]. This 319 alleviation was attributed to CUR's depressive effect on formation of 320 ROS and stimulatory effect on endogenous anti-oxidant activity by 321 its free radical scavenging property [42][43][44]. 322…”
mentioning
confidence: 99%
“…The sample preparation was based on a procedure described elsewhere [39]. Bi(NO3)3 was mixed with deionized water, and the ascorbic acid and EDTA were then added.…”
Section: Sample Preparationmentioning
confidence: 99%